2021
DOI: 10.1080/20009666.2020.1857510
|View full text |Cite
|
Sign up to set email alerts
|

Remdesivir in a pregnant patient with COVID-19 pneumonia

Abstract: Remdesivir is an antiviral drug currently being studied as a potential treatment of pneumonia caused by infection with SARS-CoV-2. The Adaptive Covid-19 Treatment Trial (ACTT-1) by NIH and the SIMPLE study by Gilead Sciences are two major trials that showed promising results of Remdesivir in the non-pregnant population. We are presenting the case of a pregnant patient who was diagnosed with COVID-19 pneumonia and successfully treated with Remdesivir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 13 publications
(11 reference statements)
0
26
0
5
Order By: Relevance
“…Entre os estudos escolhidos, encontramos cinco relatos de caso descrevendo o papel do Remdesivir no tratamento da Covid-19 (Dubert et al, 2020;Dande et al, 2021;Helleberg et al, 2020;Tempestilli et al, 2020;Igbinosa et al 2020).…”
Section: Resultsunclassified
“…Entre os estudos escolhidos, encontramos cinco relatos de caso descrevendo o papel do Remdesivir no tratamento da Covid-19 (Dubert et al, 2020;Dande et al, 2021;Helleberg et al, 2020;Tempestilli et al, 2020;Igbinosa et al 2020).…”
Section: Resultsunclassified
“…Among 20 case reports describing antiviral treatment, sixteen pregnant women received the antiviral remdesivir. [9][10][11][12][13][14][15][16][17] The dose of remdesivir given was a regimen of 200 mg intravenous (IV) on day 1 followed by 100 mg IV daily. Duration of administration of remdesivir varies, from 2 until 10 days, this difference in the duration of administration depends on the improvement in clinical symptoms and side effects such as increase of aspartate transaminase levels, transaminitis, and hepatitis that occur when given remdesivir.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the adverse effects the There are also some other studies listed in the literature that have shown safe use of remdesivir with positive outcomes during pregnancy. 1,5,8,10,11…”
Section: Discussionmentioning
confidence: 99%